(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Diabetes mellitus is one of the most common endocrine metabolic disorders and significantly impacts the health, quality of life, and life expectancy of patients as well as on the healthcare system. Herbal remedies are convenient for managing diabetes due to their traditional acceptability and availability, low cost, and fewer side effects. The study aimed to evaluate the anti-diabetic effects of ethanolic extract of Momordica dioica leaf in normal and streptozotocin (STZ)-induced diabetic rats. In the study, two doses of ethanolic extracts of Momordica dioica leaf (MDL) were administered to normal rats for an oral glucose tolerance test. For anti-diabetic studies in STZ-induced diabetic rats, the effects of extracts were observed for duration of 28 days for blood glucose alterations. After the completion of the experimental period, the experimental rats were sacrificed and the collected serum samples were subjected to various biochemical parameter studies, including lipid profile, glycosylated hemoglobin (HbA1c), urea, and creatinine level studies. Whereas the tissues collected were subjected to antioxidant studies followed by histopathological studies of the pancreas. In this research study, it was observed that the MDL extracts showed a significant reduction in blood glucose level, reverted the altered lipid profile, and increased HbA1c to normal. It significantly normalized the urea and creatinine levels, as well as levels of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH). Thus, from this study, it could be concluded that MDL extract exhibited potent anti-diabetic activity in STZ-induced diabetic rats. This significant activity may be due to the presence of gallic acid, rutin, charntin, ferulic acid, and ellagic acid.